Alternative splicing of pre-mRNA modulates the immune response in Holstein cattle naturally infected with Mycobacterium avium subsp. paratuberculosis - Badia-Bringué, Gerard; Lavín, José Luis; Casais, Rosa; Alonso-Hearn, Marta (Frontiers in Immunology, 2024)
Little is known about the role of alternative splicing (AS) in regulating gene expression in Mycobacteria-infected individuals in distinct stages of infection. Pre-mRNA AS consists of the removal of the introns and the assembly of exons contained in eukaryotic genes. AS events can influence transcript stability or structure with important physiological consequences. Using RNA-Seq data from peripheral blood (PB) and ileocecal valve (ICV) samples collected from Holstein cattle with focal and diffuse paratuberculosis (PTB)-associated histopathological lesions in gut tissues and without lesions (controls), we detected differential AS profiles between the infected and control groups. Four of the identified AS events were experimentally validated by reverse transcription-digital droplet PCR (RT-ddPCR). AS events in several genes correlated with changes in gene expression. In the ICV of animals with diffuse lesions, for instance, alternatively spliced genes correlated with changes in the expression of genes involved in endocytosis, antigen processing and presentation, complement activation, and in several inflammatory and autoimmune diseases in humans. Taken together, our results identified common mechanisms of AS involvement in the pathogenesis of PTB and human diseases and shed light on novel diagnostic and therapeutic interventions to control these diseases.